Financial Re-Engineering and Customer Performance of Poultry Business in Nigeria - Alawode, Olufemi Peter; Nwobodo, Helen; Ogunfowora, Afolake; Olubunmi, Alao; Onyeka-Iheme, Chimeruo Victory (International Journal of Economics and Financial Issues, 2024)
The poultry business is the largest private sector employer and contributes 25% to Nigeria’s agricultural gross domestic product. The process of capturing poultry business performance using the balanced scorecard performance pillar of customer performance had not been completely integrated in prior research. Therefore, this study looked at how financial re-engineering affected the customer performance of the chicken industry in Nigeria using proxies for business strategy, business processes and systems, business technology, organizational structure, and organizational culture. The study adopted survey research design. The population of the study were 4324 active farmers and support services of the key poultry business stakeholders in the six geo-political zones of Nigeria. The sample size of 450 was determined using Taro Yamane sample size formula. Strata random sampling technique were used to select the respondents from the geo-political zones. A structured and valid questionnaire, using 5 level Likert-scale, were administered to the respondents with a response rate of 84%. The Cronbach’s alpha reliability coefficients for the constructs ranged from 0.87 to 0.95. Descriptive and inferential (multiple regression) analysis were used to analyse the data at 5% level of significance. The findings revealed that all financial re-engineering exerted significance effect on customer performance (Adj.R2 = 0.520 F(5,379) = 82.950, P < 0.05). The study concluded that financial re-engineering has significant effect on customer performance of poultry business in Nigeria and recommended that poultry business owners and management in Nigeria should integrate financial re-engineering into their processes in order to optimize production and attract premium customers with attendant total performance expectations.